Combined effects of organic amendments and fertilization on cotton growth and yield. (28th September 2022) - Adeli, Ardeshir; Brooks, John P.; Miles, Dana; Misna, Todd; Feng, Gary; Jenkins, Johnie N.
Abstract: With escalating fertilizer prices, interest in using poultry litter as a source of plant nutrients has increased. However, the rapid decomposition of litter, particularly in the hot and humid southern United States, makes poultry litter vulnerable to loss of nutrients. Biochar and lignite have been proposed to mitigate nutrient loss, particularly N. However, information on the integration of biochar and lignite with poultry litter on cotton ( Gossypium hirsutum L.) growth and yield is limited under southeastern agro‐ecosystems. A field experiment was conducted on a Leeper silty clay loam soil from 2017 to 2020 to evaluate the combined effect of poultry litter and inorganic N fertilizer with biochar and lignite on cotton growth, yield, and nutrient utilization. The treatments consisted of a 3 × 3 full‐factorial arrangement of amendments and fertilization types organized in a randomized complete block design. Application rates were 6.7 Mg ha –1 for poultry litter, 6.7 Mg ha –1 for biochar and lignite, and 134 kg N ha –1 for inorganic fertilizer. Lignite and biochar were only added once. The combination of biochar and lignite with poultry litter and inorganic fertilizer was positively effective on yield and yield components. Integration of biochar with poultry litter and inorganic fertilizer increased lint yield by 42 and 44% as compared with fertilization alone. Cotton leaf area index increased by 34 and 51% when biochar and lignite were combined with inorganic fertilizer in 2020. The leaching loss of postharvest soil NO3 –N was significantly reduced by 66 and 50% when biochar and lignite were combined with inorganic fertilizer, respectively. Core Ideas: Combined biochar and lignite with poultry litter increased cotton yield. Integration of biochar and lignite with fertilization reduced NO3 –N leaching loss. Poultry litter and inorganic fertilizer produced similar lint yield.